2016
DOI: 10.1115/1.4034755
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of High Energy Ball Milling on the Structure and Properties of LiNi1/3Mn1/3Co1/3O2 Cathodes for Li-Ion Batteries

Abstract: Particle size plays an important role in the electrochemical performance of cathodes for lithium-ion (Li-ion) batteries. High energy planetary ball milling of LiNi1/3Mn1/3Co1/3O2 (NMC) cathode materials was investigated as a route to reduce the particle size and improve the electrochemical performance. The effect of ball milling times, milling speeds, and composition on the structure and properties of NMC cathodes was determined. X-ray diffraction analysis showed that ball milling decreased primary particle (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Electrodes were fabricated from a slurry composed of 80 wt% active material (typically ~150-200 mg of sample), 10 wt% conductive carbon (TIMCAL Super C65), and 10 wt% binder (Arkema, Kynar HSV900 -5% in N-Methyl-2-pyrrolidinone (NMP)) using a similar method previously reported[47]. Excess NMP was added to control the viscosity of the slurry.…”
mentioning
confidence: 99%
“…Electrodes were fabricated from a slurry composed of 80 wt% active material (typically ~150-200 mg of sample), 10 wt% conductive carbon (TIMCAL Super C65), and 10 wt% binder (Arkema, Kynar HSV900 -5% in N-Methyl-2-pyrrolidinone (NMP)) using a similar method previously reported[47]. Excess NMP was added to control the viscosity of the slurry.…”
mentioning
confidence: 99%
“…Since a variety of materials are blended by high‐energy ball milling, improper milling times and/or speeds will more or less break the structural integrity of spherical secondary particles. [ 111 ] Besides, the types of coating materials used in dry coating process are generally composed of nanoparticles, which tend to aggregate on the surface of cathode materials, protecting some areas but leaving other areas exposed (Figure 3). To maximize the protective areas, more nanoparticles need to be deposited to form a complete but thick coating layer, which can be as thick as 100 nm.…”
Section: Applications Of Coating In Ni‐rich Materialsmentioning
confidence: 99%
“…Taleghani et al also performed studies on the effect of particle size distributions on cell performance. Stein et al performed various studies on how particle size affects the cell performance [12] and showed that the planetary ball milling of electrode materials resulted in smaller crystallite size. However, the benefits of the size reduction were found to be limited in some cases, with intermediate crystallite sizes showing better overall performance due to reduced agglomeration and lower interfacial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the performance of thick electrodes can be enhanced by increasing the porosity and decreasing the tortuosity of the electrodes [16]. Other parameters related to electrode structure and particle size can influence battery performance [12,13].…”
Section: Introductionmentioning
confidence: 99%